2020
DOI: 10.21608/pssjn.2020.94763
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Nurses' Performance Regarding Care of Patients Undergoing Cardiac Catheterization

Abstract: Background: Nurses have a variety of roles and functions associated with the patients' care undergoing cardiac catheterization. Nurses provide care of a patient before, during, and after cardiac catheterization procedure. Aim: This study aimed to assess nurses' performance regarding care of patients undergoing cardiac catheterization. Subjects and Method: A descriptive research design was conducted. Setting: At cardiac catheterization unit at Port Said general hospital in Port-Said City and Al-Azhar university… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…This might be appertain level of qualification of the nurses under study as majority of them were got bachelor degree and approval of procedure book, protocol & policy regarding patients' safety after CC in CCU. This finding is supported by Bakr (2020) [6] study about " assessment of nurses' performance regarding care of patients undergoing cardiac catheterization." and found that their knowledge was satisfactory, While, Sajila, (2013) [26] who conducted a study about" Assessment of nurses knowledge regarding the care of patients undergoing CC among nurses in selected hospital in Bangalore" and found that their knowledge was moderately adequate.…”
Section: Second Part Nurses' Knowledge Regarding Patients' Safety Aft...mentioning
confidence: 61%
“…This might be appertain level of qualification of the nurses under study as majority of them were got bachelor degree and approval of procedure book, protocol & policy regarding patients' safety after CC in CCU. This finding is supported by Bakr (2020) [6] study about " assessment of nurses' performance regarding care of patients undergoing cardiac catheterization." and found that their knowledge was satisfactory, While, Sajila, (2013) [26] who conducted a study about" Assessment of nurses knowledge regarding the care of patients undergoing CC among nurses in selected hospital in Bangalore" and found that their knowledge was moderately adequate.…”
Section: Second Part Nurses' Knowledge Regarding Patients' Safety Aft...mentioning
confidence: 61%
“…[21]. The results of another study by Bakr et al (2020) revealed that implementing a training program for nurses would improve their knowledge and practice of caring for patients with head injuries. The study recommended that a regular training program for nurses caring for patients with head injuries be implemented in hospitals, emphasizing the importance of implementing a training program for nurses to reduce the incidence of complications of head injuries [22].…”
Section: Resultsmentioning
confidence: 99%
“…The results of another study by Bakr et al (2020) revealed that implementing a training program for nurses would improve their knowledge and practice of caring for patients with head injuries. The study recommended that a regular training program for nurses caring for patients with head injuries be implemented in hospitals, emphasizing the importance of implementing a training program for nurses to reduce the incidence of complications of head injuries [22]. Aloush et al(2018) conducted another study that found that providing periodic training to nurses working in intensive care units to improve their competence and progress in the workplace is very useful and e cient [23].…”
Section: Resultsmentioning
confidence: 99%
“…Our research has overcome some limitations by performing the studies in three specilaty heart and interventional cardiovascular hospitals in Ho Chi Minh City compared to previous studies. These hospitals are the frontline heart hospitals in the southern region of Vietnam with relatively distinct public and private models, therefore, there is an existence of extrapolation value compared to previous studies [7,[14][15][16].…”
Section: Knowledge Of Nurses On Patient Safety After Cag or Pcimentioning
confidence: 99%